A Facile Liquid Phase Exfoliation of Tungsten Diselenide using Dimethyl Sulfoxide as Polar Aprotic Solvent to Produce High‐quality Nanosheets. Issue 3 (11th February 2021) - Kashyap, Pradeep Kumar; Kumar, Ashish; Srivastava, Ritu; Gupta, Sarika; Gupta, Bipin Kumar
Abstract: Two‐dimensional (2D) ultra‐thin nanosheets of semiconducting layered structure of transition metal dichalcogenides (TMDs) are in high demand for fundamental studies as well as potential applications in optoelectronic devices, advanced display devices and many more. The real challenge in this area is to produce large scale nanosheets with a single stable phase.Herein, we report a top‐down strategy for liquid‐phase exfoliation of bulk tungsten diselenide (WSe2 ) powder to produce hexagonal (2H) few layers (2–3 layers) of nanosheets by ultra‐sonication method using a highly‐efficient dimethyl sulfoxide (DMSO) as polar aprotic solvent. As produced nanosheets are further characterized by different spectroscopic techniques such as Raman and ultraviolet‐visible (UV‐Vis) spectroscopy to validate the quality of exfoliated WSe2 nanosheets and estimated the direct optical band gap after exfoliation of WSe2 . Further, the Raman spectroscopy evidences the transition from bulk to few layers of WSe2 nanosheets. The TEM/HRTEM images and XPS results also confirm the good quality and efficient exfoliation of WSe2 nanosheets. Moreover, the estimated optical band gap from UV‐Vis and Tauc plot confirm the transition occurs from indirect band gap (∼1.27 eV) to direct optical band gap ∼1.55 eV after exfoliation of WSe2 nanosheets. Hence, the proposed method provides a simple, large scale and inexpensive exfoliation approach to produce high‐quality single phase 2H‐WSe2 nanosheets. Abstract : A facile liquid phase exfoliation of WSe2 using DMSO polar aprotic solvent to produce high‐quality nanosheets has been demonstrated. Raman and UV‐Vis spectroscopies confirm the quality of exfoliated WSe2 nanosheets and conversion of indirect band gap to direct band gap after exfoliation. Thus, this new approach provides a simple and inexpensive exfoliation approach to produce high‐quality single phase 2H‐WSe2 nanosheets.